2009
DOI: 10.1016/j.mce.2009.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin treatment protects lactotrophs from apoptosis in the pituitary of diabetic rats

Abstract: Poorly controlled diabetes is associated with hormonal imbalances, including decreased prolactin production partially due to increased lactotroph apoptosis. In addition to its metabolic actions, ghrelin inhibits apoptosis in several cell types. Thus, we analyzed ghrelin's effects on diabetes-induced pituitary cell death and hormonal changes. Six weeks after onset of diabetes in male Wistar rats (streptozotocin 70 mg/kg), mini-pumps infusing saline or 24 nmol ghrelin/day were implanted (jugular). Rats were kill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 75 publications
3
16
0
Order By: Relevance
“…Indeed, several studies have demonstrated the requirement of BCL2 in protection against b-cell apoptosis (Rabinovitch et al 1999, Kim et al 2008). Our results are consistent with previous findings on the antiapoptotic action of AG, UAG, and Ob in a variety of cell types, including pancreatic b-cells (Baldanzi et al 2002, van der Lely et al 2004, Granata et al 2006, Granado et al 2009). However, we could not detect apoptosis in the islets of STZ-treated rats after 70 days of treatment, probably because STZ-induced b-cell apoptosis is an early event, occurring within few hours of STZ administration (Yamamoto et al 1981, Morimoto et al 2005.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, several studies have demonstrated the requirement of BCL2 in protection against b-cell apoptosis (Rabinovitch et al 1999, Kim et al 2008). Our results are consistent with previous findings on the antiapoptotic action of AG, UAG, and Ob in a variety of cell types, including pancreatic b-cells (Baldanzi et al 2002, van der Lely et al 2004, Granata et al 2006, Granado et al 2009). However, we could not detect apoptosis in the islets of STZ-treated rats after 70 days of treatment, probably because STZ-induced b-cell apoptosis is an early event, occurring within few hours of STZ administration (Yamamoto et al 1981, Morimoto et al 2005.…”
Section: Discussionsupporting
confidence: 93%
“…Besides the stimulation of GH release, ghrelin affects several important biological functions including appetite, food intake and energy balance, cardiovascu lar function, reproduction, and bone growth (Asakawa et al, 2001;Pemberton and Richards, 2008;Wren et al, 2000 ). Several reports suggest that ghrelin inhibits apoptosis and oxidative damage in various tissues (Granado et al, 2009;Kui et al, 2009;Lau et al, 2009;Obay et al, 2008;Sehirli et al, 2008 ). More specifically, ghrelin has been shown to protect gastric mucosa against stress and ischemia-re perfusion induced gastric injury (Brzozowski et al, 2004;Konturek et al, 2006 ) to enhance gastric motility and gastric emptying (Trudel et al, 2002;Tumer et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the stimulation of GH release, ghrelin participates in a variety of physiological activities such as cardiovascular function, food intake, and energy balance, appetite, bone growth, and reproduction (18). It has been shown that ghrelin prevents oxidative damage and apoptosis in different tissues (19)(20)(21). It was also proved that ghrelin protects gastric mucosa against gastric injury caused by stress and ischemia-reperfusion and that it improves gastric motility and gastric emptying (22,23).…”
Section: Introductionmentioning
confidence: 99%